撮影画像を平行化する画像変換プログラム、装置及び方法 (2017)
PROBLEM TO BE SOLVED: To provide an image transformation program, device, and method capable of highly accurately parallelizing images captured by a camera.SOLUTION: In the captured image, an identification code given to a subject is imaged. The image transformation program for parallelizing the captured images includes: point correspondence calculation means for calculating a point correspondence of feature points between any arbitrary representative image and each slave image regarding a plurality of captured images; plane projective transformation matrix calculation means for calculating a plane projective transformation matrix between the representative image and each slave image for each point correspondence; bird's eye view image candidate calculation means which estimates a parallelization parameter by using each plane projective transformation matrix, and outputs a plurality of bird's eye view image candidates by converting the representative image into a bird's eye view image while using each of the parallelization parameters; and code read determination means for outputting a bird's eye view image for which image-like reading of the identification code is made successful, as a parallelized bird's eye view image from among the plurality of bird's eye view image candidates.